The Role of Investment Banks in Acquisitions - Servaes, Henri; Zenner, Marc (Review of Financial Studies, 1996)
We compare acquisitions completed with and without investment bank advice over the 1981 to 1992 period. We find that the choice to use an investment bank depends on the complexity of the transaction, the type of transaction (takeovers versus acquisitions of assets), the acquiror’s prior acquisition experience, and the degree of diversification of the target firm. Although acquisition announcement returns are lower for firms using investment banks, this difference can be explained by differences in transaction characteristics. These results suggest that transaction costs are the main determinant of investment banking choice, followed by contracting costs and asymmetric information costs.